Level of Digital Competences and the Examination the Relationship Between Unemployment and in Job-Trainings in the European Union - Csordás, Adrián; Füzesi, István (International Journal of Engineering and Management Sciences, 2019)
In this study we examined the digital competences by the EU Member States between 2015 and 2017 based on data of OECD and EuroStat. We wanted to know, are there any relationship between the unemployment and the level of digital competences. We realised that, in these countries where the percentage of individuals with basic digital skills is higher, there the harmonized unemployment rate is lower, than in those states where the individuals have above-average digital skills. In the case of lower educated states (where the citizens do not have a general digital knowledge), the unemployment rate is higher. We researched the openness of companies towards individuals with different levels of digital knowledge. In these countries, where the more educated people live there provide the comapnies more chance to take part further trainings, than in the less educated countires. We found a moderately strong negative correlation between the group of individuals who have low overall digital skills and in-work trainings. It means, if a country has individuals with a few digital competences, there the organisations will not offer trainings them. According to the available data we could divide the EU Member States in three clusters. These groups are underdeveloped, developing, developed countries. The biggest difference is between these groups in the quantity of skilled people, however the distribution of individuals in the developed group also shows interesting features. We realised in these countries the so-called „reverse competence pyramid”. It means, as the level of skill grows, the number of individuals, who own it, grows as well. As a continuation of the research, it would be worth examining the countries regionally, so it would be clear where are, the "digital kingdoms" can be found. On the one hand this could help the state in the allocation of digital education, on the other hand, it would also improve the position of companies. They could create regional centers in less developed countries, thus outsourcing expensive high added value work.